Existence uniqueness and stability for certain operators of nonlinear system of differential equations - Abdullah , Dawoud .S; Rafeeq, Ava; Butris , Raad N. (Bulletin of Social Informatics Theory and Application, 2023)
This research contributes to the understanding of nonlinear systems of differential equations with operators, specifically in the context of generalizing Volterra and Fredholm integral equations. The use of the Picard approximation method, Banach fixed point theorem, and stability analysis further enhances the analysis of the solutions. The examples provided help to solidify the theoretical findings and highlight their applicability.